SFL-BASED ANALYSIS OF THEMATIC PROGRESSION OF ENGLISH GRADUATE PERSONAL STATEMENTS - Haji, Ghada (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The main problem faced by graduate and undergraduate students in writing their university application letters includes the difficulties of producing a coherent and cohesive text that can convince the evaluators of their suitability to the target program. The present study was conducted principally to investigate the thematic progression patterns realized in students’ statements (henceforth PSs), for their considerable role in shaping the overall structure of the text and unfolding the writer’s identity. The corpus consists of 20 PSs written by graduate English students applying for a Master's in Sociology in Western institutions. Eggin’s (2004) framework of Theme and Rheme was applied to analyze the thematic progression patterns (TPP) observed and find out the dominant pattern revealed from the students’ texts. The findings of the analysis indicated the presence of two main thematic progression patterns, namely the Reiteration pattern and Zigzag pattern, with the total absence of the Multiple theme pattern. The obtained results of this work may offer valuable insights for academic writing instructions and material developers.